Persiapan Sekolah Menghadapi Kurikulum Berbasis Kompetensi - Margono Margono (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2003)
Competence Based Curriculum (KBK) came along with the reformation movement which demanded democratization, decentralization, and autonomy. KBK has several characteristics, i.e.: as minimal curriculum of national standard, fun learning atmosphere, classroom based assessment, and school-based curriculum management. Prior to its implementation, schools need to sharpen their vision and mission, analyze the students’ and schools’ ability, develop syllabus, increase teachers’ ability related to learning models, equip themselves with learning facilities, and change the principals’ leadership styles.